APRESENTAÇÃO DOS CADERNOS DO IL 57 - Almeida, Ana Luiza Nunes; Simionato, Deborah Mondadori; Cyrino, Lucas; da Costa, Monica Chagas; Hoff, Patrícia Cristine (Cadernos do IL, 2018)
APRESENTAÇÃO DOS CADERNOS DO IL 57